2004
DOI: 10.1007/s00467-003-1402-z
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin and renal impairment in neonates

Abstract: Renal impairment occurs in neonates receiving indomethacin for treatment of patent ductus arteriosus. Inhibition of cyclooxygenase within the neonatal kidney results in decreased prostaglandin synthesis and consequent reduction in renal perfusion. Indomethacin has been reported to cause short-term reduction in glomerular filtration that resolves after cessation of the drug. There is little information on the long-term effects of postnatal exposure to indomethacin. The aim of this study was to determine the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 20 publications
6
55
0
1
Order By: Relevance
“…In a study on infants of <30 weeks gestation, a significant decrease in glomerular filtration rate was noted on days 2 and 7 after administration of indomethacin. 45 Some previous studies have shown a decline in peak systolic and mean velocities in SMA after its administration. 45,46 On the other hand, the theoretical benefit of therapeutic intervention relates to enhanced intestinal perfusion by minimizing transductal flow, therein reducing ductal steal.…”
Section: Ductal Steal and Nonsteroidal Anti-inflammatory Agentsmentioning
confidence: 95%
“…In a study on infants of <30 weeks gestation, a significant decrease in glomerular filtration rate was noted on days 2 and 7 after administration of indomethacin. 45 Some previous studies have shown a decline in peak systolic and mean velocities in SMA after its administration. 45,46 On the other hand, the theoretical benefit of therapeutic intervention relates to enhanced intestinal perfusion by minimizing transductal flow, therein reducing ductal steal.…”
Section: Ductal Steal and Nonsteroidal Anti-inflammatory Agentsmentioning
confidence: 95%
“…Adverse physiological consequences of indomethacin on the cerebral, renal and/or intestinal circulation have been demonstrated in animal and human studies [5][6][7][8] .…”
Section: Indomethacin and Coronary Blood Flowmentioning
confidence: 99%
“…Both of these drugs are successful in closing the ductus (3,4), but the morphologic effects these drugs may have on the developing kidney are unknown. Both drugs are known to be nephrotoxic, with indomethacin causing acute renal failure in 25% of premature neonates treated (5). Ibuprofen is considered to have less renal toxicity than indomethacin, but is as efficacious as indomethacin at closing the patent ductus (6).…”
mentioning
confidence: 99%